Biodegradation of crude oil by individual bacterial strains and a mixed bacterial consortium - Santisi, Santina (Braz J Microbiol, 2015)
Three bacterial isolates identified as Alcanivorax borkumensis SK2, Rhodococcus erythropolis HS4 and Pseudomonas stutzeri SDM, based on 16S rRNA gene sequences, were isolated from crude oil enrichments of natural seawater. Single strains and four bacterial consortia designed by mixing the single bacterial cultures respectively in the following ratios: (Alcanivorax: Pseudomonas, 1:1), (Alcanivorax: Rhodococcus, 1:1), (Pseudomonas: Rhodococcus, 1:1), and (Alcanivorax: Pseudomonas: Rhodococcus, 1:1:1), were analyzed in order to evaluate their oil degrading capability. All experiments were carried out in microcosms systems containing seawater (with and without addition of inorganic nutrients) and crude oil (unique carbon source). Measures of total and live bacterial abundance, Card-FISH and quali-, quantitative analysis of hydrocarbons (GC-FID) were carried out in order to elucidate the co-operative action of mixed microbial populations in the process of biodegradation of crude oil. All data obtained confirmed the fundamental role of bacteria belonging to Alcanivorax genus in the degradation of linear hydrocarbons in oil polluted environments.